Restoration of glutamate delta 1 signaling and excitatory inhibitory imbalance in the central amygdala in cisplatin induced neuropathic pain by cerebellin 1 - Gajanan P. Shelkar; Sukanya G. Gakare; Kishore Kumar S. Narasimhan; Poojashree B. Chettiar; Devansh G. Asati; Shriti S. Thakur; Shashank M. Dravid (Scientific Reports)
Abstract Glutamate delta-1 receptor (GluD1) is an unusual member of ionotropic glutamate receptor family which plays a role in formation and maintenance of synapses. We have previously found enriched expression of GluD1 at the parabrachioamygdala synapses and its crucial role in fear and pain modulation. Here we demonstrate that GluD1-cerebellin 1 (Cbln1) signaling within the central amygdala (CeA) is crucial for neuroplasticity and hyperalgesia observed in chemotherapy-induced neuropathic pain (CINP). We found that CINP was associated with an increase in excitatory neurotransmission and an opposing decrease in inhibitory neurotransmission in the laterocapsular region of CeA (CeLC). CINP was also associated with a decrease in GluD1 and Cbln1 in the CeA which was observed over 5 weeks of CINP. To address the causal relationship of downregulation of GluD1-Cbln1 signaling to excitatory-inhibitory imbalance and hyperalgesia we examined the effect of intra-CeA administration of recombinant Cbln1 (250 ng/side). This treatment alleviated mechanical hypersensitivity in CINP mice. Notably, intra-CeA administration of recombinant Cbln1, normalized excitatory-inhibitory imbalance in the CeLC neurons. The reduced inhibitory neurotransmission in CINP could be attributed to reduced GABAregic output from somatostatin neurons which was normalized by recombinant Cbln1. Our results underscore the pivotal role of GluD1-Cbln1 signaling in the CeA region in CINP and provide insights into strategies that could potentially mitigate the severe side effects associated with cisplatin treatment.